Scaffold architecture for dental biomaterials: influence of process parameters on the structural morphology of chitosan electrospun fibers - Joyce Rodrigues de Souza; Tabata Prado Sato; Alexandre Luiz Souto Borges (Brazilian Dental Science)
Objective: The electrospinning is a widely adopted technique used to produce the polymeric fibers. The process depends on process parameters (voltage, flow rate and distance from capillary to the collector). The present study aimed to evaluate the influence of these parameters on chitosan fibers, a biopolymer used as scaffolds in dental and oral tissue engineering. Material and Methods: A solution of 7%(m/w) was prepared dissolving 0.7g of chitosan in 7 mL of trifluoroacetic acid (TFA) and 0.3mL of dichloromethane (DCM) (TFA/DCM - 70:30). After 12 hours, polymer solution (5 mL) was drawn into the syringe and pumped through needles of 0.4 mm internal diameter, at a rate of 0.8 mLh-1, different needle-tip-to-collector distances and voltages, for 10 min.  Electrospun fibers micrographies were obtained using the Scanning Electron Microscope for morphological analysis. Results: All voltages showed significant difference (p < 0.0001) between them. At 15kV fibers showed higher concentration of beads. At 10 and 12 cm of distance there was no statistical significance (p > 0.0001) but at 15 cm beads formation increased significantly (p < 0.0001). At 12 cm fibers showed lowest fibers diameter in comparison to 10 and 15 cm (p < 0.0001). There was no difference between 10 and 12 cm (p > 0.0001) but in comparison to 15 cm both distances presented significantly difference (p < 0.0001).  Conclusion: Thus, it can be concluded that morphology, in chitosan electrospun fibers, is influenced by the voltage and distance and this could describe the mohphological control of these structures.